On a possibility of usage of the scalar impedances for solving the inverse MTS problem for three-dimensional models - Prichepiy, T. I. (Geofizicheskiy Zhurnal, 2016)
A review of the results of calculating of seeming specific resistance for a set of elementary models by scalar impedance method, in particular, by impedance parameter z has been given in the article. The values of electromagnetic field parameters of the models have been calculated by the Mackie 1994 program. According to this method of calculation the field is excited by flat low-frequency homogeneous electromagnetic wave. Calculation of electromagnetic field parameters for each model object was accomplished for a set of values of T periods. Specific resistances calculated by scalar impedance z, are presented as a graphs rz(x) and isolines fields across the observations area. The results obtained for the given class of models have shown a possibility to restore the conducting characteristics of lower half-space without determining the impedance tensor Ž and predetermined a possibility of further development of this method not only for visualization of data but also for obtaining numerical solutions of the inverse MTS problem.